Sodium Bicarbonate Ingestion Improves Time-to-Exhaustion Cycling Performance and Alters Estimated Energy System Contribution: A Dose-Response Investigation - Gurton, William H.; Gough, Lewis A.; Sparks, S. Andy; Faghy, Mark A.; Reed, Katharine E. (Frontiers in Nutrition, 2020)
This study investigated the effects of two sodium bicarbonate (NaHCO3) doses on estimated energy system contribution and performance during an intermittent high-intensity cycling test (HICT), and time-to-exhaustion (TTE) exercise. Twelve healthy males (stature: 1.75 ± 0.08 m; body mass: 67.5 ± 6.3 kg; age: 21.0 ± 1.4 years; maximal oxygen consumption: 45.1 ± 7.0 ml.kg.min-1) attended four separate laboratory visits. Maximal aerobic power (MAP) was identified from an incremental exercise test. During the three experimental visits, participants ingested either 0.2 g.kg-1 BM NaHCO3 (SBC2), 0.3 g.kg-1 BM NaHCO3 (SBC3), or 0.07 g.kg-1 BM sodium chloride (placebo; PLA), 60 minutes pre-exercise. The HICT involved 3 x 60 s cycling bouts (90%, 95%, 100% MAP) interspersed with 90 s recovery, followed by TTE cycling at 105% MAP. Blood lactate was sampled after each cycling bout to calculate estimates for glycolytic contribution to exercise. Gastrointestinal (GI) upset was quantified at baseline, 30 minutes and 60 minutes post-ingestion, and 5 minutes post-exercise. Cycling TTE increased for SBC2 (+20.2 s; p =0.045) and SBC3 (+31.9 s; p =0.004) compared to PLA. Glycolytic contribution increased during the TTE protocol for SBC2 (+7.77 kJ; p =0.10) and SBC3 (+7.95 kJ; p =0.07) compared to PLA. GI upset was exacerbated post-exercise after SBC3 for nausea compared to SBC2 and PLA (p <0.05), whilst SBC2 was not significantly different to PLA for any symptom (p >0.05). Both NaHCO3 doses enhanced cycling performance and glycolytic contribution, however, higher doses may maximise ergogenic benefits.